Cultivation and Marketing Knowledge level of Areca nut Farmers in Andaman & Nicobar Islands - Kasinath, B L; Meena, B L; Kumar, Shailesh; Lal, Shardul Vikram; Kapoor, P; Gangaiah, B (Journal of Extension Education, 2020)
Areca nut (Areca catechu L) also known as betel nut or supari is the second most important plantation crop of Andaman and Nicobar Islands (ANI) after coconut It has been observed that wide differences in productivity of areca nut exist among the farmers with in a village due to socio-economic status. A survey based study was conducted to understand the knowledge level of areca nut growers and link to productivity vis-a-vis socio-economic status. For this purpose, 120 areca nut farmers from four villages of Harinagar Panchayat were randomly selected. Data collected were analysed following standard statistical procedures. The results showed that 52.5% of areca nut growers had poor knowledge of cultivation and marketing. The study also revealed that about 45% growers had poor knowledge about selection of suitable site, soil and spacing requirement for plants. The analysis of socio-economic factors with knowledge level of farmers revealed that knowledge of respondents increased with the increase in their education and land holdings whereas it was negatively correlated with age and annual income. Further, the study also suggests that, educating the farmers through mass media, capacity building and demonstration will help them in learning/ adopting new technologies, which in turn help them to increase their productivity level and farming income on sustainable basis.